ETHNOGRAPHY OF YOUTH LEARNING (Proceedings of the International Conference on Public Health, 2017)
The purpose of this qualitative study aimed to study learning of youth through the community volunteering spirit process in a socio-cultural context. The study was conducted in one municipality located in Sra-kaew province from December 2015 to October 2016. This study employed critical ethnography method as the research design and it was divided into 3 phases: 1) exploring the community to understand socio-cultural context, 2) studying the situation or event contributing youth volunteering spirit, and characteristic of youth volunteer in a community and 3) analyzing the outcome or learning of youth from the development of volunteerism system in youths by community.The participants were divided into 2 groups, including 42 key informants and 19 general informants. The data were collected using participant observation, in-depth interviews and focus group discussions, and analyzed by content analysis.  The results indicated as follows. 1) The incidents and event causing youth volunteerism; Problems and needs in the community, National and local policies, Cultural practice, Cultural activities. 2) Five characteristics of the volunteering work of the youth; Sociological, Economical, Environmental, Health-related and Political characteristics 3) Seven Outcome from volunteer worked
Keywords: youth, volunteering spirit, youth’s learning